DEMOGRAPHIC TRANSITION AT THE REGIONAL LEVEL IN CZECH LANDS - AVRAM, Cristina (Economy and Sociology, 2021)
This study presents the results of the development of demographic transition at the regional level in the Czech Lands. The analysis uses data from censuses and vital statistics. The period for analysis is 1869-1935, and the data was recalculated for the 2011 administrative division. In the study, we used the classical approach of analysis of the demographic processes. This article aims, first, to show the evolution of mortality and fertility levels at the regional level during the demographic transition, and second, to show that the demographic transition in the Czech lands follows the patterns of other European countries, but with some particularities at the regional level.